Pengaruh Reminding melalui Whatsapp Terhadap Kepatuhan Minum Obat pada Pasien Tuberkulosis Paru - Saputra, Yovi Agus; Apriliany, Fitri; Ramdhany, Muh. Wisda Praja (Department of Pharmacy, Bumigora University, 2024)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. M. tuberculosis enters the body through inhaled air and spreads in the lungs. In 2021, Mataram City detected a total of 739 tuberculosis cases. Many tuberculosis patients still exhibit low adherence to taking their medication. This research investigates the influence of WhatsApp reminders on medication adherence in pulmonary tuberculosis patients. This is an analytical observational study with a quasi-experimental design that employs a prospective pre-test and post-test approach. The data for this study was collected from outpatient patients at RSUD Kota Mataram. The result indicates a significant improvement in medication adherence among pulmonary tuberculosis patients, with a significant value of the Wilcoxon test (p = 0.000, <0.05). The conclusion drawn from this study is that reminders through WhatsApp influence medication adherence in pulmonary tuberculosis patients at RSUD Kota Mataram.